(untitled) (CIPEEX, 2025)
This paper presents information on bullying practices and the increase in cyberbullying1 due to the growth in the use of social networks and digital media itself. Awareness and preventive actions related to these practices require efforts from the whole of society in order to prevent situations from reaching the point of extreme punishment, especially after the enactment of the law that criminalized such conduct. Through awareness, education, and sensitization, it is possible to create a healthier environment of respect and safety for everyone. The focus should be on building environments where all children and adolescents can develop without fear of being intimidated or excluded, an obligation imposed by the State on all educational establishments. 1 Term given to the practice of bullying on the internet and social media.